2021
DOI: 10.3390/medicina57050480
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life T-14 Outcomes for Pediatric Bizact Tonsillectomy

Abstract: Objectives: The objective of this study was to assess the T-14 outcomes of the BizactTM device for tonsillectomy in a pediatric population. Methods: A case series chart review was undertaken at a public tertiary teaching hospital and private otolaryngology practice, with data collected from pediatric patients who underwent a BizactTM tonsillectomy between July 2016 and October 2019 for any indication, whose parents consented to completing the T-14 questionnaire providing a parental perspective of the child’s q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Studies have mainly investigated health status before and after an applied treatment by using detailed questionnaires. Recurrent tonsillitis and tonsil hypertrophy, (and its complications), are believed in many countries to reduce the quality of life in children so affected ( 19 – 29 ). These studies emphasize that limitations in children's health affect joint family activities, physical activity, general health, behaviour and family emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have mainly investigated health status before and after an applied treatment by using detailed questionnaires. Recurrent tonsillitis and tonsil hypertrophy, (and its complications), are believed in many countries to reduce the quality of life in children so affected ( 19 – 29 ). These studies emphasize that limitations in children's health affect joint family activities, physical activity, general health, behaviour and family emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an enlarged adenoid may impair the patency of the Eustachian tube which, inter-alia , can lead to exudative otitis media, that may lead to hearing loss ( 47 53 ). Symptoms of tonsil hypertrophy are: snoring, obstructive sleep apnea syndrome, speech disorder (slurring) and dysphagia; especially with solid foods ( 19 35 , 49 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have mainly investigated children's health status before and after an applied treatment by using detailed questionnaires. In many countries, recurrent tonsillitis and tonsil hypertrophy (and its complications) are recognized as reducing the quality of life of affected children [19][20][21][22][23][24][25][26][27][28][29]. These studies emphasize that limitations in a child's health affect joint family activities, physical activity, general health, behaviour, and family emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an enlarged adenoid may impair the patency of the Eustachian tube which, inter alia, can lead to exudative otitis media, that may lead to hearing loss [49][50][51][52][53][54][55]. Symptoms of tonsil hypertrophy are snoring, obstructive sleep apnea syndrome, speech disorders such as slurred speech, and dysphagia (especially with solid foods) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]51,55].…”
Section: Discussionmentioning
confidence: 99%
“…Each participant served as their own control and were followed longitudinally to determine changes in their QoL. We have previously reported that the T-14 questionnaire has high compliance with parents and is suitable for Australian patients undergoing tonsillectomy, as well as its use in assessing clinical efficacy of the BiZact tonsillectomy device [ 14 , 24 ]. This study has demonstrated that parents perceive their child’s symptoms do not significantly change while waiting for elective surgery.…”
Section: Discussionmentioning
confidence: 99%